2004
DOI: 10.4141/p02-157
|View full text |Cite
|
Sign up to set email alerts
|

Early seeding dates improve oat yield and quality in the eastern prairies

Abstract: . 2004. Early seeding dates improve oat yield and quality in the eastern prairies. Can. J. Plant Sci. 84: 431-442. Demand for high quality oat (Avena sativa L.) for consumption by humans and race horses has increased, leading to increased oat production on the Canadian prairies. Little information exists on the best management practices for producing high-quality, high-yielding oat using direct seeding systems and cropping practices developed and adopted over the past 15 yr. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Browne et al (2006) deduced that oat yield can vary with increasing rates of N, while mean grain weight remains relatively stable due to changes in number of panicles per square metre and number of grains per panicle. Grains per panicle has been identified as being associated strongly with cultivar (May et al 2004b). The number of panicles per square metre varied somewhat among cultivars of oat depending on location (Table 5), although the cultivar with the greatest number of productive tillers per unit area did not necessarily have a yield advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Browne et al (2006) deduced that oat yield can vary with increasing rates of N, while mean grain weight remains relatively stable due to changes in number of panicles per square metre and number of grains per panicle. Grains per panicle has been identified as being associated strongly with cultivar (May et al 2004b). The number of panicles per square metre varied somewhat among cultivars of oat depending on location (Table 5), although the cultivar with the greatest number of productive tillers per unit area did not necessarily have a yield advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Lodging is a concern in oat as it has the potential both to slow harvest of the crop, and to reduce yield and quality. Declines in oat quality parameters including kernel weight, test weight and groat yield have been associated with increased lodging, particularly with laterseeded oat crops (May et al 2004a). …”
Section: Crop Lodgingmentioning
confidence: 99%
“…Whereas the specific set of quality parameters required to achieve a highquality oat varies depending upon the market (e.g., whether for human consumption or horse feed), higher test weights and kernel plumpness are two factors that may garner price premiums (May et al 2004a). The objective of this study was to determine the effect of various rates and combinations of N, P and KCl fertilizers on the yield and quality of oat grown in Manitoba.…”
mentioning
confidence: 99%
“…Oat grain yield usually declines when seeding is delayed after the middle or end of May in western Canada. May et al (2004a) found that delaying seeding until the middle of June compared with the beginning of May resulted in an average yield loss of 43%. The largest yield losses associated with delayed seeding came in oat varieties that were susceptible to the plant pathogen crown rust (Puccina coronata Corda f. sp.…”
mentioning
confidence: 99%
“…In addition to yield reductions caused by delayed seeding, quality reductions also occur. May et al (2004a) noted that kernel weight, test weight and plump seed all declined as seeding was delayed into June. These oat physical quality metrics are important in the selection of milling oat.…”
mentioning
confidence: 99%